Free Vibrations and Flexural Strength Analysis of 3D Architected Core Sandwich Polymer - K. Mayandi, Sethuramalingam, B. Ramanan, Nadir Ayrilimis, N. Rajini, R. Pranesh Raju, M. Rajkumar (International Journal of Control and Automation, 2020)
This article focuses on the new 3D Printing (3DP) manufacturing technique. The object of this paper is the mechanical properties (flexural and free vibration analysis), based on fused filament production with fused deposition modelling (FDM), of materials created by 3D Printing. Polylactic acid (PLA) and Wood-PLA materials had chosen for this research work. This article explains the effect of 3D fabrication on flexural properties and free vibration analysis of the different layer height with two pattern style of PLA and Wood-PLA. The additive production, also known as 3D fabricating, is a typical method of extrusion of material using PLA (bio) polymers.PLA (Polylactic Acid) is bio-degradable and bioactive polyester made up of lactic acid building blocks. Due to the low print temperature PLA is most commonly used in 3D printers and is more suitable for parts with fine detail and easy to print. Wood PLA is a composite material in which has wood particles combined with the PLA. Here in this paper, the properties of these two materials are tested and compared with flexural and the free vibration tests. These two materials had tested after making a 3D architected sandwich core model and testing the model in the ANSYS workbench. The comparisons from the observed data indicate that PLA has a better energy absorbing capability and also deforms in a less amount than Wood-PLA.